Reducing risk of development or exacerbation of nutritional deficits by optimizing patient access to mealtime assistance. (22nd December 2019) - Teeling, SeÁn Paul; Coetzee, Heather; Phillips, Maeve; McKiernan, Mary; NÍ ShÉ, ÉidÍn; Igoe, Aileen
Abstract: Objective: Optimize patient access to mealtime assistance, decrease missed meal incidence, risk of malnutrition, reduce food waste and staff rework. Design: Lean Six Sigma methodology informed a pre/post intervention design. Setting: 31 bed ward including Specialist Geriatric services and Acute Stroke Unit within an Irish University teaching hospital. Participants: Clinical and non-clinical staff including catering, nursing, speech and language therapy, dietetics and nutrition; patients, relatives. Interventions: An interdisciplinary team used the structured Define/Measure/Analyse/Improve/Control (DMAIC) framework to introduce visual aids and materials to improve the access of patients to assistance at mealtimes. Main outcome measures: Pre and post outcomes measures were taken for the number and cost of uneaten meals, rework for staff, staff and patient satisfaction, patient outcomes. Results: Following a 1-month pilot of a co-designed process for ensuring access to assistance at mealtimes, average wasted meals due to staff not being available to assist patients requiring mealtime assistance went from 3 per day to 0 corresponding to an average reduction of 0.43 kg per participating patient in food waste per day. Patients receiving assistance did not require additional oral therapeutic nutritional supplements, evidenced no new incidences of aspiration pneumonia or swallowing difficulties and were discharged without requirement for ongoing Dietetics and Nutrition support. Following a 6 month Control period comprising repeated PDCA cycles, the initiative was incrementally introduced to a further 10 wards/units, with positive feedback from patients and staff alike. Conclusion: The co-designed new process highlights the importance of staff and patient collaboration, inclusion and participation in designing quality improvement projects.